2018
DOI: 10.1111/sdi.12696
|View full text |Cite
|
Sign up to set email alerts
|

Clinical problems in hemodialysis patients with autosomal dominant polycystic kidney disease

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is a common monogenic disease characterized by massive enlargement of fluid-filled cysts in the kidney. Due to its genetic pattern, the disease differs from other CKD. ADPKD is a multi-system, progressive disorder which is frequently complicated with hypertension, cardiovascular events and cerebrovascular disease. Thus, there are many clinical problems specific to ADPKD. In this article, we reviewed these clinical problems and their management in ADPKD with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 135 publications
(294 reference statements)
1
1
0
Order By: Relevance
“…It is a major modifiable cardiovascular risk factors but also a factor in the progression of chronic kidney disease. The diagnosis of hypertension is made early International Journal of Nephrology and Kidney Failure and at a younger age compared to patients with essential hypertension [7,8]. In our study, the familial nature of the disease was established in 50% of patients, a result close to that found in Najoua with 57% of cases [6].…”
Section: Discussionsupporting
confidence: 67%
“…It is a major modifiable cardiovascular risk factors but also a factor in the progression of chronic kidney disease. The diagnosis of hypertension is made early International Journal of Nephrology and Kidney Failure and at a younger age compared to patients with essential hypertension [7,8]. In our study, the familial nature of the disease was established in 50% of patients, a result close to that found in Najoua with 57% of cases [6].…”
Section: Discussionsupporting
confidence: 67%
“…97 However, PD is an anticoagulation-free treatment modality providing reduced risk of intracerebral bleeding in cases with the presence or possibility of intracranial aneurysms. 98 Accumulating evidence also showed that technique and/or patient survival is similar or better in ADPKD patients with PD in comparison to those with HD. 94,[99][100][101][102][103][104] As a result, there is little evidence that ADPKD is a contraindication for PD.…”
Section: Polycystic Kidney Diseasementioning
confidence: 99%